Activitatea lui N. I. Lobacevski ca bibliotecar (Confluenţe Bibliologice, 2015)
The article tells about the great Russian mathematician who made a huge contribution to the development of library science. He laid the foundations for the acquisition of library collections, initiated the creation of unified catalogues and international book exchange.